A backpack γ-spectrometer for measurements of ambient dose equivalent rate, H˙∗(10), from 137Cs and from naturally occurring radiation: The importance of operator related attenuation. (December 2017) - Ramzaev, V.; Bernhardsson, C.; Barkovsky, A.; Romanovich, I.; Jarneborn, J.; Mattsson, S.; Dvornik, A.; Gaponenko, S.
Abstract: This study is devoted to the calibration of a backpack radiation detection system (BPRDS) for evaluation of the external dose to a person staying in an environment contaminated by 137 Cs. A commercially available portable gamma-ray spectrometer-dosemeter based on a NaI(Tl) detector was used. By means of information in the pulse-height distribution, it has been possible to separate the technogenic and natural components of the ambient dose equivalent rate, H ˙ ∗ ( 10 ), (ADER). In situ measurements were made in the Bryansk region (Russia) and Gomel region (Belarus) in 2015–2016. Both regions had been severely contaminated by 137 Cs due to the Chernobyl nuclear accident in 1986. Background measurements were performed at those regions of Russia that received negligible amounts of Chernobyl fallout. Measurements were made inside and outside settlements at typical outdoor locations: street, yard, arable land, undisturbed grassland and forest. The ADER in the pack-back geometry for an operator with a body mass of about 70 kg and a height of 170 cm was 12% lower than the ADER registered in the standard measurement geometry with the detector placed on a tripod at a height of 1 m above ground. The attenuation of the primary 662 keV photons from 137 Cs in the operator was measured as a 22% reduction of ADER. Much smaller effect, on average 3–4% reduction, was observed with respect to ADER due to scattered photons from 137 Cs in the environment. The BPRDS and calibration factors have been used during walking surveys in two Russian settlements with 137 Cs ground deposition densities in 1986 of about 80 kBq m −2 (village of Zatishie) and 700 kBq m −2 (town of Novozybkov). The ADER due to natural terrestrial radionuclides and 137 Cs were in the ranges 15–50 nSv h −1 and 14–500 nSv h −1, respectively. The man-made source dominates total ADER in forests, while contribution from the natural sources prevails in the ADER recorded above paved areas. Highlights: Calibration of a gamma-ray spectrometer for backpack measurements. Measurements of ambient dose equivalent rates due to 137 Cs and natural radionuclides. Estimation of the dose rates due to primary and scattered photons from 137 Cs. Intercomparison of measurements in the standard (on a tripod) and backpack geometries. The attenuation in the operator at backpack measurements is determined in situ.